The Problems of Manuscripts Management in Turkey: Proposed Solutions - Mehmet Emin Küçük (Türk Kütüphaneciliği)
This paper aims to determine and examine (in general) the problems of manuscripts management in Turkey and to provide possible solutions for the identified problems. Turkey has some very rich manuscripts collections with approximately 600,000 volumes. The collections are only thinly catalogued and at present Turkey has no national database or catalogue. As a result of this situation, these vast intellectual and histoi'ical resources are not fully exploited. In addition to the cataloguing, personnel, user services and preser-vation-restoration are the major problems of manuscripts management in Turkey. It is asserted that the present system for manuscript management is not suitable to improve the present situation and a new management system should be established. The proposals for the establishment of the new system are also provided.